2003
DOI: 10.1016/s0954-6111(03)00136-7
|View full text |Cite
|
Sign up to set email alerts
|

Airway inflammation and basement membrane tenascin in newly diagnosed atopic and nonatopic asthma

Abstract: Previous studies have shown both similar and distinct inflammatory changes in atopic and nonatopic asthma. This study was set to investigate the bronchial inflammatory cell infiltrate and subepithelial basement membrane (BM) tenascin deposition in subjects with newly diagnosed asthma and bronchial hyperresponsiveness (BHR). Seventy-nine asthmatic subjects (age 18-60 years) were recruited and 58 were atopic according to skin prick testing. The patients recorded asthma symptoms and peak flow measurements for 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
2
35
0
1
Order By: Relevance
“…[21][22][23] In atopic controls, Djukanovic et al showed that these changes are similar in nature but less marked compared with those in atopic asthmatic subjects. 23 In elite winter athletes, increases in airways' tenascin thickness or inflammatory cell counts were observed, independently of atopy, having significant airway remodeling and inflammation compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] In atopic controls, Djukanovic et al showed that these changes are similar in nature but less marked compared with those in atopic asthmatic subjects. 23 In elite winter athletes, increases in airways' tenascin thickness or inflammatory cell counts were observed, independently of atopy, having significant airway remodeling and inflammation compared with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Thickening of epithelial basement membrane has been observed as a characteristic remodeling for asthma for a long time but was also found in early asthma (Karjalainen et al 2000(Karjalainen et al , 2003. Thickening of basement membrane observed with microscopy correspond to the deposition of extracellular matrix (ECM) at subepithelial space observed by electron microscopy, and it is called subepithelial fibrosis (Roche et al 1989;Jeffery et al 1992).…”
Section: Thickening Of Epithelial Basement Membrane and Subepithelialmentioning
confidence: 99%
“…15 Patients with asthma exhibit tenascin expression near the epithelial cells. 16 Tenascin expression has also been detected in benign and malignant lung tumors, but the intensity of staining seems to be especially strong in the stroma of squamous cell carcinomas. 14,17 In usual interstitial pneumonia, tenascin is expressed in early fibrotic lesions.…”
mentioning
confidence: 99%